2004
DOI: 10.7146/math.scand.a-14450
|View full text |Cite
|
Sign up to set email alerts
|

Local dynamics of uniformly quasiregular mappings

Abstract: We investigate local dynamics of uniformly quasiregular mappings, give new examples and show in particular that there is no quasiconformal analogue of the Leau-Fatou linearization of parabolic dynamics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
72
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(73 citation statements)
references
References 23 publications
(17 reference statements)
1
72
0
Order By: Relevance
“…Now, the proof of [8,Theorem 6.3] shows that L, M are injective in neighborhoods of 0 U, V respectively. Since L and M are linearizers for f at the repelling fixed point x 0 , then L(U) ∩ M(V ) = E ∋ x 0 , which is a subset of the domain of f for which the linearization is valid.…”
Section: Relationship Between Linearizersmentioning
confidence: 99%
See 3 more Smart Citations
“…Now, the proof of [8,Theorem 6.3] shows that L, M are injective in neighborhoods of 0 U, V respectively. Since L and M are linearizers for f at the repelling fixed point x 0 , then L(U) ∩ M(V ) = E ∋ x 0 , which is a subset of the domain of f for which the linearization is valid.…”
Section: Relationship Between Linearizersmentioning
confidence: 99%
“…For such mappings, the Julia set and Fatou set can be defined and they partition space, just as in the complex case. The fixed points of uqr mappings have been classified [8] in a similar fashion to the classification of fixed points of holomorphic functions. In particular, there are repelling fixed points of uniformly quasiregular mappings.…”
Section: Quasiregular Linearizersmentioning
confidence: 99%
See 2 more Smart Citations
“…Behaviour near the fixed points of uniformly quasiregular mappings was studied in detail in [11]. There it was shown that if a uniformly quasiregular mapping is locally injective at a fixed point, then it is in fact bi-Lipschitz there, whereas typically a quasiregular mapping is only locally Hölder continuous.…”
mentioning
confidence: 99%